Efektivitas Pengawasan Badan Pengawas Obat dan Makanan terhadap Peredaran Produk Pangan Olahan Impor dalam Mewujudkan Perlindungan Konsumen - Irna Nurhayati (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2009)
This research has two purposes. First, to argue the effectiveness of control by the National Agency of Drug and Food Control concerning distribution of imported processed food products in establishing consumer protection. Second, to analyze the obstacles faced by the National Agency of Drug and Food Control in the distribution control of imported processed food products in Indonesia. The research result shows that, first: the control by the National Agency of Drug and Food Control concerning distribution of imported processed food products in establishing consumer protection in Indonesia is ineffective yet. The proof is that there are imported processed food products which are illegal and still distributed in Indonesia without permission, also unsafe to be consumed. Moreover, there are imported processed food products which contain dangerous materials and danger to be consumed even though they have license to be distributed in Indonesia. Second, the obstacles faced by the National Agency of Drug and Food Control in controlling the imported processing food products in Indonesia include two categories, the internal and external aspects.